La revolución minera asturiana de 1934 en Melania Jacoby , de Susana Pérez Alonso: Un conflicto individual de proyecciones universales - Crespo, Marcela Gladys (2015)
Susana Pérez Alonso's novel Melania Jacoby proposes two levels of meaning: on the one hand, it deals with what it means to be Asturian and its social rebelliousness, and the visible traces left in the history of the region by the Asturian revolution of 1934 as well; on the other hand, the novel can be read as a universal metaphor of two forces in conflict: the untamed Nature (represented by the sea, the fields, and the coal mines) and the efforts by men to subjugate it and put it at the service of the Asturian bourgeoisie and the incipient power of the franquists. The purpose of this article is to analyze how the figure of Melania Jacoby, a woman who transgresses the hegemonic order in terms of class and gender, acts as a point of articulation and dialogue between those conflicting forces and constitutes an “interstitial space,” a border, and a place of resistance for the marginalized people (the women, the persecuted, and the poor).